Seven perfect things : a novel - Hyde, Catherine Ryan (Lake Union Publishing, 2021)
"Abby Hubble lives in an unhappy home in the Sierra Nevada foothills where her father makes life miserable for her and her mother...One day Abby witnesses a man dump a litter of puppies into the nearby river. Diving in to rescue all seven...she takes them to an abandoned cabin...Grieving widower Elliot Colvin,...looking for solace, retreats to the hunting cabin...What he discovers is not at all what he expected: seven puppies and one determined girl with an indomitable heart. As Abby and Elliot's friendship deepens, Abby imagines how much better her life and the puppies' lives would be if her mother were married to Elliot instead of her father"--